Evaluation of Noninvasive Tools for Predicting Esophageal Varices in Patients With Cirrhosis at Tygerberg Hospital, Cape Town - Lawrence Kwape; Shiraaz Gabriel; Ahmad Abdelsalem; Penelope Rose; Lefika Bathobakae; Dale Peterson; Desiree Moodley; Mohammed Parker; Saadiq Moolla; Arifa Parker; Keatlaretse Siamisang; Christoffel Van Rensburg; et al. (International Journal of Hepatology)
Conclusion: SSM and SSPS have the highest diagnostic accuracy for predicting the presence of EVs in patients with compensated cirrhosis. LSPS, LS3PS, and PSR come second at 94%. We recommend SSM and SSPS in institutions with transient elastography equipped with the software necessary to measure splenic stiffness. We introduce and propose LS3PS as a novel composite score for predicting the presence of EVs in patients with compensated cirrhosis. Large-sample-size studies are needed to validate these prediction scores and to allow direct comparison with Baveno VII. These prediction tools can help clinicians avoid unnecessary endoscopic procedures in patients with compensated cirrhosis, especially in developing countries with limited resources such as South Africa.